Two-dimensional metal–organic frameworks with high oxidation states for efficient electrocatalytic urea oxidation. Issue 79 (20th September 2017) - Zhu, Dongdong; Guo, Chunxian; Liu, Jinlong; Wang, Liang; Du, Yi; Qiao, Shi-Zhang
Abstract : A two-dimensional metal–organic framework comprising nickel species and an organic ligand of benzenedicarboxylic acid is fabricated and explored as an electrocatalyst for urea oxidation reaction. Abstract : A two-dimensional metal–organic framework (MOF) comprising nickel species and an organic ligand of benzenedicarboxylic acid is fabricated and explored as an electrocatalyst for urea oxidation reaction (UOR). The excellent UOR performance is found to be partially due to the high active site density of the two-dimensional MOF, and largely because of the high oxidation state of the nickel species.